Towards radiocarbon dating of single foraminifera with a gas ion source - Wacker, Lukas; Lippold, Jörg; Molnár, M.; Schulz, H. (Nuclear instruments & methods in physics research. Section B, Beam interactions with materials and atoms, 2013)
Carbonate shells from foraminifera are often analysed for radiocarbon to determine the age of deep-sea sediments or to assess radiocarbon reservoir ages. However, a single foraminiferal test typically contains only a few micrograms of carbon, while most laboratories require more than 100μg for radiocarbon dating with an accelerator mass spectrometry (AMS) system. The collection of the required amount of foraminifera for a single analyses is therefore time consuming and not always possible. Here, we present a convenient method to measure the radiocarbon content of foraminifera using an AMS system fitted with a gas ion source. CO2 is liberated from 150 to 1150μg of carbonate in septum sealed vials by acid decomposition of the carbonate. The CO2 is collected on a zeolite trap and subsequently transferred to a syringe from where it is delivered to the ion source. A sample of 400μg (50μgC) typically gives a 12C− ion source current of 10-15μA over 20min, yielding a measurement precision of less than 7 per mil for a modern sample. Using this method, we were able to date a single 560μg Cibicides pseudoungerianus test at 14,030±160 radiocarbon years. Only a minor modification to our existing gas handling system was required and the system is fully automatable to further reduce the effort involved for sample preparation.